2019
DOI: 10.1111/ppe.12568
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal paracetamol exposure and neurodevelopmental outcomes in preschool‐aged children

Abstract: Background: Recent studies have suggested an association between prenatal paracetamol exposure and adverse neurodevelopmental outcomes in children. However, these findings may be confounded by unmeasured factors related to maternal use of paracetamol and child outcomes.Objective: To examine the association between duration and timing of prenatal paracetamol exposure on parent-reported communication skills, behaviour, and temperament in preschool-aged children, with focus on the role of unmeasured confounding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 43 publications
0
54
0
Order By: Relevance
“…Given that all exposure collected in the included studies involved some degree of recall, with latency ranging from weeks to years, some degree of misclassification is inevitable. Further, several studies included self‐reported exposure and outcome data from the same source (ie maternal report), which may leave them vulnerable to dependent measurement error. If over‐reporting of exposures co‐occurs with over‐reporting of outcomes, for example, this could produce the appearance of a strong effect of exposure on outcome.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Given that all exposure collected in the included studies involved some degree of recall, with latency ranging from weeks to years, some degree of misclassification is inevitable. Further, several studies included self‐reported exposure and outcome data from the same source (ie maternal report), which may leave them vulnerable to dependent measurement error. If over‐reporting of exposures co‐occurs with over‐reporting of outcomes, for example, this could produce the appearance of a strong effect of exposure on outcome.…”
mentioning
confidence: 99%
“…In two studies, parent and teacher reports diverged, but in a third they did not, making this difficult to interpret. One study used probabilistic bias analysis to quantify the potential impact of exposure misclassification, noting that realistic levels of misclassification could have substantially attenuated the observed effect estimates. On balance, the information bias in these studies should move estimates towards the null: this is a reasonable expectation with dichotomous exposures.…”
mentioning
confidence: 99%
See 3 more Smart Citations